2007
DOI: 10.2174/156652307780859035
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy in Peripheral Nerve Reconstruction Approaches

Abstract: Gene transfer to a transected peripheral nerve or avulsed nerve root is discussed to be helpful where neurosurgical peripheral nerve reconstruction alone will not result in full recovery of function. Axonal regeneration is supposed to be facilitated by this new therapeutic approach via delivery of specific regeneration promoting molecules as well as survival proteins for the injured sensory and motor neurons. Therefore gene therapy aims in long-term and site-specific delivery of those neurotrophic factors. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Owing to the ability to control protein expression levels, the incorporation of gene switches into gene therapeutic regimens may render those therapies currently under development more effective, and also enable wider extension among indications in cancer, [7] cardiovascular diseases, [8,9] diabetes, neurodegenerative disorders, [10,11] motor neuron diseases, muscular dystrophy, [12] cystic fibrosis, [13,14] neuropathic pain, [15] rheumatoid arthritis [16,17] and regenerative medicine in general. [18,19] Additionally, gene switches have biopharmaceutical applications in areas such as cell-based assays and animal models for developmental drug testing, as well as biotherapeutics and biomaterials production. [20] Among the various available gene-switch platforms, the insect ecdysteroidregulated switches are refractory to human endogenous steroids, and typically show very low basal transgene expression, high inducibility, and broad dose-response gradation-usually outperforming other systems in each of these aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the ability to control protein expression levels, the incorporation of gene switches into gene therapeutic regimens may render those therapies currently under development more effective, and also enable wider extension among indications in cancer, [7] cardiovascular diseases, [8,9] diabetes, neurodegenerative disorders, [10,11] motor neuron diseases, muscular dystrophy, [12] cystic fibrosis, [13,14] neuropathic pain, [15] rheumatoid arthritis [16,17] and regenerative medicine in general. [18,19] Additionally, gene switches have biopharmaceutical applications in areas such as cell-based assays and animal models for developmental drug testing, as well as biotherapeutics and biomaterials production. [20] Among the various available gene-switch platforms, the insect ecdysteroidregulated switches are refractory to human endogenous steroids, and typically show very low basal transgene expression, high inducibility, and broad dose-response gradation-usually outperforming other systems in each of these aspects.…”
Section: Introductionmentioning
confidence: 99%
“…The genetically engineered BMSCs could potentially be transplanted within tissue-engineered nerve conduits, as has been successfully done before with genetically engineered Schwann cells. 4 In order to compare the feasibility of optimized NTF delivery increasing the neurite outgrowth in vitro, we utilized adult DRG explant organotypic cultures as well as neonatal DRG drop cultures. The DRG neurite outgrowth model is widely used to assess the neurite outgrowth in a specific environment.…”
Section: Discussionmentioning
confidence: 99%
“…cultures were maintained for 1 day. (C) a density of 30×10 4 egFP-Pc-12 cells was mixed with either np-NTFs or 40×10 4 nT-BMscs or FgF-2 18kDa -BMscs in a volume of 1 ml 0.5% NVr-gel (containing Pc-12 cell differentiation medium) and transferred into a 24-multiwell culture well. cultures were maintained for 5 days.…”
Section: Pc-12 Differentiation Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most promising strategies for local growth factor delivery is probably gene trans-fer and this approach is also getting more and more interest in the repair of the peripheral nervous system (Haastert and Grothe, 2007;Tannemaat et al, 2009;Zacchigna and Giacca, 2009;Pereira Lopes et al, in press). Various studies in animal models have shown that peripheral nerve regeneration can be improved by gene trans-fer.…”
Section: Tissue Engineering Of Peripheral Nervesmentioning
confidence: 99%